GENDER AND GOVERNANCE OF THE REINTEGRATION OF RETURNEE REFUGEE WOMEN IN LIBERIA (2011)
Studies indicated that women and men experience conflict, displacement and return differently. In post-war contexts, gender aspects of returnee reintegration have however not been adequately addressed by researchers and policy makers. This study, therefore, examined the gender aspects of the governance of reintegration of returnee refugee Liberian women. It identified the challenges and factors affecting reintegration. Qualitative methods of data collection were employed. One hundred in-depth interviews (IDIs) were conducted with men and women purposively selected from five of Liberia's fifteen administrative counties, comprising both rural and semi-urban areas. Participants included stakeholders in the governance of returnee refugee reintegration such as government officials, representatives of non-governmental organizations (NGOs), donor agencies and returnee refugees. The IDIs were supplemented with six focus group discussions with returnee women and men, and documentary review. Reliability and validity were achieved by triangulation, inter-observer reliability and respondent validation. The data collected were subjected to content analysis. The governance of the reintegration of returnee refugees involved a combination of governmental agencies and NGOs with severe problems of coordination. The Liberian Refugee Repatriation and Resettlement Commission and the Ministry of Gender and Development were not able to provide the enabling condition for returnee safety and dignity. These agencies were very weak in coordinating the activities of NGOs or mobilizing funds as they suffered from fund shortages and skill capacity deficits. Returnee refugees experienced great economic hardships, particularly with respect to access to livelihood and basic amenities such as water, healthcare and education. Consequently, there were constant backflows. Saddled with domestic responsibilities, and challenged by stayee resentments, sexual exploitation, molestation of their children and spousal abandonment, women lacked time and requisite skills to search for and secure jobs. Most of the women were unable to provide documentation to back up claims of ownership of property and were therefore disadvantaged in the midst of widespread tension over land ownership. Women returnee refugees that enjoyed extended family support had greater sense of security and safety than those without such support. Organisations such as the Women of Liberia Peace Network and the Liberian Agency for Community Empowerment mobilized women to participate in national elections and got them involved in various community and economic empowerment projects. Other issues that affected the reintegration process included limited knowledge of the security and legal system, poor implementation of the changes made in the inheritance and rape laws, the top-down approach supported by donors which limited the opportunities available to women, and the non-use of returnee skills transfer. The reintegration of returnee refugee women in Liberia was gender biased, determined by the differential effects of the cultural and social contexts on women and men. Although efforts have been made to empower women, the social division of labour and the limited opportunities for women advancement threaten the success, balance and sustainability of reintegration. It is recommended that government and donor agencies involve returnee women in reintegration policy formulation, and promote synergy between organisations working for short-term reintegration, and those working for long-term development in Liberia.